PERANCANGAN PURWARUPA RANGKA, BONCENGAN, DAN TEMPAT BATERAI SEPEDA LIPAT LISTRIK UNTUK PRODUKSI MENGGUNAKAN PENGECORAN PASIR - Hafif Romadhon; Ikhwan Taufik (ELEMEN : JURNAL TEKNIK MESIN, 2025)
Electric folding bikes are a modern transportation solution that offers practicality and efficiency of storage space. Production alternatives are needed to reduce dependence on pipes and welding processes. One alternative production process is to use the metal casting method. This study aims to design and analyze the strength the design of the frame, pillion, and battery holder of the electric folding bicycle for the metal casting process. The material used is A356 aluminum. The design and simulation process is carried out using CAD and CAE software. The loading simulation was conducted under real load conditions with a load of 99,5 kg. Based on the results of simulation and analysis, the design of the frame, bonnet, and battery compartment of the best electric folding bicycle has a von Mises stress value of 61,21 MPa, displacement of 1,712 mm, mass of 4,6 kg, and safety factor of 4,5.